How wide is a stream? Spatial extent of the potential "stream signature" in terrestrial food webs using meta‐analysis. Issue 1 (1st January 2014) - Muehlbauer, Jeffrey D.; Collins, Scott F.; Doyle, Martin W.; Tockner, Klement
Abstract : The magnitude of cross‐ecosystem resource subsidies is increasingly well recognized; however, less is known about the distance these subsidies travel into the recipient landscape. In streams and rivers, this distance can delimit the "biological stream width, " complementary to hydro‐geomorphic measures (e.g., channel banks) that have typically defined stream ecosystem boundaries. In this study we used meta‐analysis to define a "stream signature" on land that relates the stream‐to‐land subsidy to distance. The 50% stream signature, for example, identifies the point on the landscape where subsidy resources are still at half of their maximum (in‐ or near‐stream) level. The decay curve for these data was best fit by a negative power function in which the 50% stream signature was concentrated near stream banks (1.5 m), but a non‐trivial (10%) portion of the maximum subsidy level was still found >0.5 km from the water's edge. The meta‐analysis also identified explanatory variables that affect the stream signature. This improves our understanding of ecosystem conditions that permit spatially extensive subsidy transmission, such as in highly productive, middle‐order streams and rivers. Resultant multivariate models from this analysis may be useful to managers implementing buffer rules and conservation strategies for stream and riparian function, as they facilitate prediction of the extent of subsidies. Our results stress that much of the subsidy remains near the stream, but also that subsidies (and aquatic organisms) are capable of long‐distance dispersal into adjacent environments, and that the effective "biological stream width" of stream and river ecosystems is often much larger than has been defined by hydro‐geomorphic metrics alone. Limited data available from marine and lake sources overlap well with the stream signature data, indicating that the "signature" approach may also be applicable to subsidy spatial dynamics across other ecosystems.